FEATURES OF THE PARTICIPANTS COPING STRATEGY IN LIQUIDATION OF THE CHORNOBYL ACCIDENT CONSEQUENCES AND THE PARTICIPANTS IN THE ANTI-TERRORIST OPERATION - Гресько, Марина Володимирівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2018)
The article presents the results of the assessment of the radiation threat perception and a retrospective analysis of the participants coping strategy in the liquidation of the Chernobyl accident consequences, participants in the antiterrorist operation and the comparison group. It has been revealed that more than 70% of the participants in the liquidation of the Chernobyl accident consequences and more than 30% of the participants in the Anti-terrorist operation have hypertrophied perception of the radiation threat. Respondents with hypertrophied perception of the radiation threat authentically have worse self-evaluation of overall health. Features of participants coping strategy in the liquidation of the Chernobyl accident consequences are the use of emotionally focused behavior strategies. With a combination of stress factors of evacuation and ionizing radiation, the liquidators also use problem-focused strategies. Participants of ATO more often use non-adaptive emotionally-directed strategies of behavior. Emotionally-focused behavior strategies have a positive correlation with the radiation hazard factor and mental disorders.